Analisis Kepuasan Sistem Akademik Menggunakan Pendekatan Unified Theory of Acceptance and Use of Technology di IKesT Muhammadiyah Palembang - Ahmad Firdaus; Arif Fadilah (IKesT Muhammadiyah Palembang, 2023)
Backgorund : IKesT Muhammadiyah Palembang is a change in the form of the Muhammadiyah Palembang College of Health Sciences which operates in the field of health education services, then on August 5 2020 STIKes Muhammadiyah Palembang became the Muhammadiyah Palembang Institute of Health Sciences and Technology by adding educational services in the field of technology. The ongoing Revolution Era 4.0 has made information technology the main point in institutional development. The use of Information Technology in the activities carried out by IKesT MP is a main priority in prioritizing and introducing information technology to the community, especially students. Information Technology development begins with the development of an Academic Information System which includes information, data and campus academic services. Research Method: This research uses quantitative analysis techniques with the Unified Theory of Acceptance and Use of Technology (UTAUT) approach to assess the behavior of academic information system users. Results: The research results can provide an overview of the performance of academic information systems. Conclusion: The conclusion of this research is to assist institutions in developing a more optimal academic information system.